(untitled) (Circe de clásicos y modernos, 2018)
Facing an iberoamerican context that, on the one hand, pretends to remove the Ancient Greek and Latin studies in our universities, while, on the other, continues to defend them with eurocentric arguments, we propose a defense based on a committed iberomerican pluralism and multiculturalism, trying to prove that removing them implies denying an important part of our identity and subjugating ourselves to the hegemonic Western culture, but also that defending them by the traditional arguments implies contributing to the cultural colonization of our region and giving an argument in favor of their absence of the curricula of our universities.